POLISH BOOK AT THE EVE OF THE RESTORATION OF INDEPENDENCE IN 1918: POLITICAL, CULTURAL AND LEGAL CONDITIONS - KOREDCZUK, BOŻENA (Knygotyra, 2015)
In the 19th and early 20th centuries, in the territories of Poland annexed by three partitioners, books and periodicals printed in Polish played an important role in shaping and maintaining national ties among Poles living under Russian, Prussian and Austrian rules.In the period of the Partitions of Poland, all processes involving the book – printing, collecting and reading – as well as such institutions as publishing houses, bookshops and libraries were closely connected with different spheres of social life, especially politics, law and economics. That is why the situation of the Polish book on the eve of the restoration of national independence can be best captured by analysing those external, yet very important, factors. The interrelations of politics and law with the book are best reflected in publishing policies which developed under the influence of censorship, being a form of official examination of materials going to press. After the uprisings in 1830, 1863 and 1905, the partitioners tightened the legislation setting limits on Polish cultural and academic texts. As a result, on the one hand, the number of books officially published in Polish decreased and, on the other hand, the number of those published illegally increased. The most important publishing centres in the 19th century were Warsaw and Vilnius in the territory annexed by Russia, Cracow and Lviv in Austria, and Poznańin Prussia. In the Polish territories annexed by three partitioners, the control over publications varied (being strictest under Russian rule) and hence the authorities hindered the circulation of printed materials across the borders.In the 19th century, collecting Polish books and other national mementoes became very popular, which resulted in establishing private libraries rich in valuable manuscripts, incunabula, old and new prints, cartography and other special collections. The biggest of those libraries joined together and were put to public use by establishing new ones whose functioning was legally guaranteed by the foundation act. Such libraries were the Ossolińscy Library and the Bawarowscy Library in Lviv, the Ordynacja Krasińskich Library and the Ordynacja Zamojskiej Library in Warsaw, the Działyńscy Library in Kórnik, the Raczyńscy Library in Poznań, and the Ordynacja Przeździeckich Library in Czarny Ostrów in Podolia. Those institutions helped not only to preserve Polish written works, but also to compile Polish bibliography. The most important work compiled at the end of the 19th century was Bibliografia polska by Karol Estreicher (22 volumes released between 1872–1908). When Poland regained its independence in 1918, a lot of enterprises involving the book, which had been started during the period of the Partitions, were continued.